Characterizing the Mechanical Properties of Ectopic Axonal Receptive Fields in Inflamed Nerves and Following Axonal Transport Disruption. (1st March 2020) - Goodwin, George; Bove, Geoffrey M.; Dayment, Bryony; Dilley, Andrew
Highlights: Nociceptors develop ectopic axonal receptive fields following neuroinflammation and axonal transport disruption. Ectopic axonal receptive fields have low mechanical activation thresholds and produce graded responses. Mechanically sensitive ion channel blockers attenuate mechanically induced responses from ectopic axonal receptive fields. The transport of TRPV1 and TRPA1 is disrupted in inflamed nerves and following localised vinblastine treatment. There is an increased functional presence of TRPV1 and TRPA1 in axons that develop ectopic mechanical sensitivity. Abstract: Radiating pain is a significant feature of chronic musculoskeletal pain conditions such as radiculopathies, repetitive motion disorders and whiplash associated disorders. It is reported to be caused by the development of mechanically-sensitive ectopic receptive fields along intact nociceptor axons at sites of peripheral neuroinflammation (neuritis). Since inflammation disrupts axonal transport, we have hypothesised that anterogradely-transported mechanically sensitive ion channels accumulate at the site of disruption, which leads to axonal mechanical sensitivity (AMS). In this study, we have characterised the mechanical properties of the ectopic axonal receptive fields in the rat and have examined the contribution of mechanically sensitive ion channels to the development of AMS following neuritis and vinblastine-induced axonal transport disruption. In both models, there was a positive force–discharge relationship and mechanical thresholds were low (∼9 mN/mm 2 ). All responses were attenuated by Ruthenium Red and FM1-43, which block mechanically sensitive ion channels. In both models, the transport of TRPV1 and TRPA1 was disrupted, and intraneural injection of agonists of these channels caused responses in neurons with AMS following neuritis but not vinblastine treatment. In summary, these data support a role for mechanically sensitive ion channels in the development of AMS.